Erythropoietin Promotes Functional Recovery and Enhances Nerve Regeneration after Peripheral Nerve Injury in Rats - Yin, Z.-S.; Zhang, H.; Gao, W. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: EPO has been shown to have beneficial effects in a variety of CNS injury models. The purpose of this study was to evaluate the effects of EPO on nerve regeneration and functional recovery in a rat model of peripheral nerve surgery. MATERIALS AND METHODS: The sciatic nerve of the rat with a 10-mm defect was bridged with a silicone rubber tube. Forty adult male Sprague-Dawley rats were assigned to the control or experimental groups to receive an intraperitoneal injection of NGF (2000 U/kg daily for 2 weeks) or EPO (5000 U/kg daily for 2 weeks), respectively. Macroscopic, functional, electrophysiologic, ultraminiature, and histologic assessments of nerves were performed 4–8 weeks after surgery. RESULTS: The results showed that in EPO-treated rats, there was a significant increase in the axon diameter, myelin thickness, and total number of nerve fibers as well as the degree of maturity of regenerated myelinated nerve fibers in comparison with those rats not treated with EPO. In addition, as measured by the SFI and MNCV, the motor function of the re-innervated hind limbs of rats with EPO treatment significantly improved at week 8, whereas there was no significant difference in the motor function between the 2 groups at 4 weeks. CONCLUSIONS: Our results demonstrated that EPO is able to enhance nerve regeneration and promote functional recovery after peripheral nerve injury in the rat, suggesting the potential clinical application of EPO for the treatment of peripheral nerve injury in humans. CNScentral nervous systemEPOerythropoietinEPOREPO receptorIgGimmunoglobulin GIODintegrated optical attenuationMNCVmotor nerve conduction velocityMODmean optical attenuationNGFnerve growth factorPBSphosphate buffered solutionPGP 9.5protein gene product 9.5SEMstandard error of the meanSFIsciatic function indexSPSSStatistical Package for the Social Sciences